Vitamin D deficiency predicts the no-reflow phenomenon in STEMI patients undergoing primary percutaneous coronary intervention. (14th October 2021) - Verdoia, M; Gioscia, R; Viglione, F; Rolla, R; Viola, O; Brancati, M F; Solda', P L; Marcolongo, M; De Luca, G
Abstract: Background: Vitamin D displays a broad spectrum of cardioprotective effects, preventing oxidative stress, inflammation and thrombosis and improving endothelial function. Previous studies have associated vitamin D deficiency with more extended and severe coronary artery disease (CAD) and worse outcome, and especially among patients with ST-segment elevation myocardial infarction (STEMI). Few data have been reported on the association of vitamin D levels with the features of infarct-related lesions and PCI outcomes. Aim: We aimed at assessing the relationship between vitamin D and angiographic findings and the procedural results of primary percutaneous coronary intervention (pPCI) in STEMI. Methods: A consecutive cohort of patients admitted for STEMI treated with pPCI were included. The levels of 25(OH)D were assessed at admission by chemiluminescence immunoassay kit LIAISON® Vitamin D assay. Hypovitaminosis D was defined for 25(OH)D <10 ng/ml. Results: We included in our study 450 patients, divided according to tertiles values of 25(OH)D. Lower vitamin D was associated to higher use of diuretics (p=0.02), higher levels of white blood cells and glycemia (p<0.001), lower prevalence of lesions on bifurcations (p=0.03) and smaller diameter of the target coronary vessel (p=0.03). Procedural characteristics and pre-procedural TIMI flow were not different according to vitamin D levels, but for a higher rate of slow-flow/no-reflow phenomenon (12.8% vs 8.1% vs 5.3%, p=0.03, adjusted OR [95% CI]=2.6 [1.05–6.6], p=0.04 for I vs III tertile), requiring higher use of adenosine (p=0.006) and glycoprotein IIbIIIa inhibitors (p=0.01). Conclusion: The present study shows that among patients with STEMI undergoing pPCI, lower levels of vitamin D indepently predict the occurrence of slowflow/no-reflow phenomenon. Future dedicated studies will shed light on the prognostic implications of hypovitaminosis D in these patients and the potential therapeutic perspectives. Funding Acknowledgement: Type of funding sources: None.